Fifteen Years of Right to Information Act in India: A Long Way to Go - Singh, Pushpraj (The Age of Human Rights Journal, 2021)
The passing & enactment of Right to Information Act, 2005 in India has been rightly considered as a milestone in the evolution of Indian Parliamentary Democracy which attempted to ensure transparency & good governance at the grass root levels by making the public authorities accountable & responsible. This Act liberated the harassed commoners who now had a very potent weapon to seek information which had hitherto remained suppressed in the dusty files of Babus (Bureaucrats) under the garb of official secrecy & confidentiality. However, in spite of many initial success stories over a period of time this Right to Information act has been losing its effectiveness & potency as it has failed to adopt the dynamism of complex Socio-Political realities. This paper attempts to give an overview & explain the history of RTI in India, its present status, limitations/drawbacks /challenges & and suggests some remedial measures to ensure its relevance in the rapidly transforming geo political context.